DARE Newsletter, Vol. 10, Nos. 2/3, Spring/Summer 2007 - DARE; O'Cain, Ray; Hall, Joan Houston; Sorenson, Jon E. (Dictionary of American Regional English, 2007)
Contents: "Home-State Advantage" by Ray O'Cain; "From the Chief Editor's Desk" by Joan Houston Hall; "Cassidy Honored by Colleague"; "In Memoriam: Mary Ann Pels"; "Volunteer Profile: Lee York"; "Funding Update" by Jon E. Sorenson; "DARE Editor Again Honors Students"; "Coming in Volume V"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English--Dialects--United States